Combination of gas/steam turbine power cycle and fusion energy - Lê Chí Kiên; Lê Kim Long (Journal of Technical Education Science, 2013)
Electrical power is produced from power plants which uses fossil fuels (coal, oil, gas etc.) or new energies such as wind, solar, biomass, nuclear energy etc. Gas turbine, stream turbine power plants which use fossil fuels, are very popular but they have some disadvantages: CO2 emissions, high fuel cost and exhaustion etc. So, many studies are proposed to improve cons. This paper will present a combination of gas/steam turbine power cycle and fusion energy, which has high efficiency, low CO2 emissions, low fuel cost and save fossil fuels.